The role of coronary collateral circulation in patients presenting with acute left main coronary artery occlusion. (14th October 2021) - Calvao, J; Braga, M; Silva, J C; Campinas, A; Alexandre, A; Brochado, B; Amador, A F; Costa, C; Pinto, R J; Proenca, T; Carvalho, M; Marques, C; et al.
Abstract: Introduction: Acute occlusion of the unprotected left main coronary artery (LMCA) is an uncommon occurrence associated with a dismal prognosis. Whereas the role of early recruited coronary collateral circulation (CC) in prognosis of ST-segment elevation acute myocardial infarction (STEMI) patients is still controversial, it seems to be important in patients with acute LMCA occlusion. This study aimed to evaluate the coronary CC in patients with acute LMCA occlusion and its impact in short and long-term outcomes. Methods: In a retrospective two-center study, we identified 7630 patients with STEMI or high-risk non-ST segment elevation myocardial infarction who underwent emergent coronary angiography between January 2008 and December 2020. Among this cohort, we analyzed 83 patients who presented with unprotected LMCA acute occlusion (Thrombolysis In Myocardial Infarction – TIMI ≤2) and classified them in 2 groups based on the degree of CC through the right coronary artery as seen in the emergent angiography: patients with no filling of collateral vessels or filling of collateral vessels without any epicardial filling of the occluded vessel [Rentrop class 0–1 (71 patients)]; and patients with partial or complete epicardial filling by collateral vessels [CC Rentrop class 2–3 (12 patients)]. Results: Compared to patients with CC Rentrop 0–1, patients with CC Rentrop 2–3 presented significantly later to medical attention (symptom to coronary angiography time 8.7 vs 4.3 hours, p=0.02). Despite that, patients with CC Rentrop 2–3 had a significantly lower prevalence of cardiogenic shock at admission (16.7 vs 57.7%, p=0.01). During hospitalization, Killip class III-IV presentation (33.3 vs 88.7%, p<0.001) and inotropic/vasopressor therapy use (25.0 vs 69.0%, p=0.01) were less frequent in CC Rentrop 2–3 patients. The CC Rentrop 2–3 group had a significantly lower in-hospital (16.7 vs 53.5%, p=0.02) and 30-day mortality (9.1 vs 52.2%, p=0.01). In patients surviving hospitalization there was no significant difference in 1-year (30.0 vs 19.4%, p=0.48) and 5-year mortality (70.0 vs 77.4%, p=0.68). Conclusion: A well-developed coronary CC was associated to lower short-term mortality in patients presenting with acute occlusion of the unprotected LMCA. Nevertheless, in patients surviving index-event, there was no difference in the long-term outcomes. Further studies are needed to clarify if clinical approach (eg. early short-term mechanical circulatory support) of patients with CC Rentrop 0–1 should be different from those with CC Rentrop 2–3 in order to improve the outcomes of the former patients. FUNDunding Acknowledgement: Type of funding sources: None.